Purchase Intention of Halal Cosmetics: The Mediating Role of Attitude - Maghfira Rizky Maulani; Nuryakin Nuryakin; Nur Hidayah (Faculty of Economic and Business, 2022)
This study investigates the effect of knowledge, religiosity, andattitude on purchase intention. A more comprehensive studymodel is considered an effort to add to the literature on the studyof halal cosmetics, which is still very limited amid the progress ofthe halal cosmetics industry in Indonesia. The millennial samplewas used in this study and then analyzed using SEM. Accordingto the result, knowledge did not significantly impact purchaseintentions but played an essential role in influencing attitudes.Meanwhile, religiosity has been proven to significantly impact andcontribute the most to determining purchase intention but wasinsignificant in influencing attitudes. Finally, the result also foundthat attitudes mediated the influence of knowledge and religiosityon purchase intention. For this reason, industry players shouldpay more attention to religiosity in promoting their products.Consumers must be given additional knowledge to influencepositive consumer behavior, encouraging purchase intention. Theimplication of this study is limited to the millennial sample ofthe halal cosmetics product in Indonesia.JEL Classification: M31, M37